1996
DOI: 10.1161/01.res.79.4.647
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-2 Decreases Metabolic Coupling and Stimulates Phosphorylation as Well as Masking of Connexin43 Epitopes in Cardiac Myocytes

Abstract: Cardiac gap junction (GJ) channels, composed of connexins, allow electrical and metabolic couplings between cardiomyocytes, properties important for coordinated action of the heart as well as tissue homeostasis and control of growth and differentiation. Fibroblast growth factor-2 (FGF-2) is an endogenous growth-promoting protein, believed to participate in the short- and long-term responses of the heart to injury. We have examined short-term effects of FGF-2 on cardiac myocyte GJ-mediated metabolic coupling, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 48 publications
2
73
0
Order By: Relevance
“…Our previous studies suggested that mitotic stimulation may result in a PKCmediated phosphorylation of Cx43 on S262 (Doble et al, 1996;Doble et al, 2000a). Whether Cx43 phosphorylation at any one site, including S262, can affect its ability to inhibit DNA synthesis is not known.…”
Section: Mitogenic Stimulation Of Cardiomyocytes Is Associated With Dmentioning
confidence: 97%
See 2 more Smart Citations
“…Our previous studies suggested that mitotic stimulation may result in a PKCmediated phosphorylation of Cx43 on S262 (Doble et al, 1996;Doble et al, 2000a). Whether Cx43 phosphorylation at any one site, including S262, can affect its ability to inhibit DNA synthesis is not known.…”
Section: Mitogenic Stimulation Of Cardiomyocytes Is Associated With Dmentioning
confidence: 97%
“…Neonatal rat cardiomyocytes were prepared from 1-day-old Sprague Dawley rat pups (obtained from the Central Animal Care Facility at the University of Manitoba) as previously described (Doble et al, 1996;Doble et al, 2000b). Our procedures followed the guidelines of the Canadian Council on Animal Care and were approved by the local Animal Care Committee of the National Research Council of Canada.…”
Section: Primary Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently used experimental approaches to demonstrate that a particular Cx is a phosphoprotein include metabolic labeling of cultured cells with 32 P followed by immunoprecipitation and alkaline phosphatase treatment, phosphoamino acid analysis (Sáez et al 1986;Takeda et al, 1989;Musil et al, 1990;Crow et al, 1990;Sáez et al, 1990;Lau et al, 1992;Goldberg and Lau, 1993;Kurata and Lau, 1994;Doble et al, 1996;Warn-Cramer et al, 1996;Mikalsen et al, 1997;Cheng and Louis, 1999) or two-dimensional phosphopeptide mapping (Sáez et al, 1990;Kurata and Lau, 1994;Díez et al, 1995;Loo et al, 1995;WarnCramer et al, 1996;Berthoud et al, 1997;Díez et al, 1998;Kanemitsu et al, 1998) in vitro phosphorylation assays using fusion proteins or synthetic peptides containing the putative phosphorylation site(s) and purified protein kinases (Sáez et al, 1990;Loo et al, 1995;WarnCramer et al, 1996;Berthoud et al, 1997;Kanemitsu et al, 1998;Shah et al, 2002;O'Brien et al, 2004;Ouyang et al, 2005;Yogo et al, 2006;Alev et al, 2008;Morel et al, 2010); treatment of cultured cells with specific protein kinase or phosphoprotein phosphatase activators or inhibitors to alter 32 P incorporation or the immunoblot pattern of connexins (Lau et al, 1992;Husøy et al, 1993;Guan et al, 1996;Berthoud et al, 1997;…”
Section: Methods Used To Demonstrate That Connexins Are Phosphoproteinsmentioning
confidence: 99%
“…Phosphoamino acid analysis indicated that hepatocyte Cx32 and Cx43 in uninfected fibroblasts were phosphorylated on seryl residues (Takeda et al, 1989;Crow et al, 1990;Sáez et al, 1990), but Cx43 was also phosphorylated in tyrosyl residues in RSV-transformed fibroblasts (Crow et al, 1990). Using metabolic labeling with 32 P, other studies described that EGF-induced phosphorylation of Cx43 on serine residues in T51B cells through activation of mitogen-activated protein kinase (MAPK) (Lau et al, 1992;WarnCramer et al, 1996), FGF-2 induced phosphorylation of Cx43 in cardiomyocytes (Doble et al, 1996), tyrosine phosphorylation of Cx43 in early passage hamster embryo fibroblast (Mikalsen et al, 1997), phosphorylation of Cx56 by PKC and Cx49 by casein kinase 1 (CK1) in lens fiber cells (Berthoud et al, 1997;Cheng and Louis, 1999). In some cases, the specific phosphorylation site has been identified in reconstituted connexons expressed in Xenopus laevis oocytes.…”
mentioning
confidence: 99%